KORELASI ANTARA AKTIVITAS OLAHRAGA DENGAN TINGKAT STRES YANG DIALAMI SISWA KELAS XI JURUSAN BUSANA BUTIK SMKN 8 SURABAYA - ANDI PRASTIYO, NURIS (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Sport activities  to constitute physical activity that be done by man as to establish physical health, mental and spiritual. Sport activities  in this case can be done at activity kind sort. Its bearing with penjasorkes, learning is done through and with sport activities . Element joy and freshness is expected can give positive impact to student. So can control spiritual's mental state negative that potentially troubles each day-to-day activity. To it, expected sport activities  can give new atmosphere to be intermediated subject duty assignment that adequately make stressed student. Stress on the dot most saturated student becomes to culminate where student in condition stressed heavy one. Since alone stress used to mean someone disability in accomplishes charge. Keywords: sport acivities, stress